(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dexamethasone is one of the most widely used glucocorticoids which has a prominent glucocorticoid with slight mineralocorticoid property. This study was performed on twenty four adult Sprague Dawley rats to evaluate the proposed effects of dexamethasone offering as intraperitoneal injection. The animals were allocated randomly into three groups of eight rats to each. The protocol of experiment was: the control group; animals are injected intraperitoneally with 2ml of distilled water, the dexamethasone 1 group; animals are injected intraperitoneally with dexamethasone 2mg/kg, and the dexamethasone 2 group; animals are injected intraperitoneally with dexamethasone 4mg/kg. The injection period extended for one month. The results illustrate that dexamethasone cause significant declination in RBC, PCV, Hb, HDL, and neutrophils besides significant elevations in WBC, eosinophils, monocytes, LDL, TC, TG, VLDL, AST, ALT, and creatinine on a direct positive proportion with the increase in dexamethasone dose comparing with control group at (P?0.05).